Analysis of cervical cytology by conventional Pap smear at a tertiary care hospital in western Maharashtra (Panacea Journal of Medical Sciences, 2025)
Background: Cervical cancer is a major health problem and an important cause of mortality in women worldwide, particularly in developing countries. It is easily detectable and hence readily preventable disease. Cervical cytology helps to reduce significantly the incidence and mortality of cervical cancer.Aims and Objective: To study and categorize cervical cytology according to “The Bethesda system for reporting cervical cytology 2014”Materials and Methods: This is an observational descriptive study, conducted in the Department of Pathology, in a tertiary care hospital from January 2016 to June 2020. A total of 1254 cervical cytology cases were studied. The clinical details were recorded from requisition forms. All the cervical cytology smears were of conventional preparation and were reported according to the Bethesda system for reporting cervical cytology 2014.Results: The present study included patients in the age range 20 - 88 years. Cervical smears which were satisfactory for evaluation were 90.51% and unsatisfactory for evaluation were 9.49%. Negative for intraepithelial lesion or malignancy cases were 1074 and 61 cases were epithelial cell abnormalities. Atypical squamous cells cannot exclude high grade squamous intraepithelial lesion (ASC-H) [32.79%] was the most common epithelial cell abnormality. Out of 108 cervical cytology cases with available histopathological examination, 99 cases showed concordant findings and 9 cases showed discordant findings.Conclusion: Cervical smear is an important, useful and simple tool for detection of precancerous lesions of cervix and should be used as a primary screening tool for early detection of cervical cancer.